The Marshall Plan and the European Integration: The Stance of Great Britain and France (1947–1948) - P. I. Falaleev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The development and implementation of the Marshall Plan has been studied quite thoroughly in both Russian and foreign academic literature. Nevertheless, certain aspects of this problematique require further examination, particularly the reaction of the Western European countries to the initiative of the Secretary of State G. Marshall, as well as the impact of the Plan on the process of the European integration in general. The paper demonstrates that this reaction was far from simple and often contradictory since the key Western states had very diﬀerent views on the future of mutual relations, as well as on the prospects for post-war recovery and development of Europe. The paper examines the evolution of the French and British leaders’ views on these issues from the ﬁrst discussions of the projects to provide US aid to Western Europe to the implementation of the Marshall Plan. The negotiations revealed signiﬁcant points of disagreement among the parties particularly regarding the relations with the USSR, the German question, and conditions for receiving assistance from the United States. The author stresses that the need to defend their interests during the course of negotiations with the US representatives contributed greatly to the rapprochement of Britain and France and, at the same time, catalyzed debates on the integration of Western Europe. In this regard the author emphasizes that the idea of regional economic integration received mixed reaction in the American elites. While some considered this process as an eﬀective means of bringing the Western countries together, particularly, over the German question, others feared that integration of Western Europe could potentially lead to the emergence of a new competitor to the USA. The author concludes that the growing popularity of integration projects in Europe in 1947–1948 stemmed from a range of factors, including both a combination of internal European political processes and short-term and long-term consequences of the Marshall Plan. Whereas in terms of economic development of Western Europe the latter were rather ambiguous and are still the subject of controversy, in terms of world politics the Marshall Plan exacerbated block-to-block confrontation in Europe, characteristic of the Cold War period.